REKONSTRKSI HUKUM KEDALAM PERTANGGUNGJAWABAN TINDAK PIDANA KORPORASI SEBAGAI PELAKU TINDAK PIDANA LINGKUNGAN HIDUP - Cako, Jofi; Gultom, Elfrida Ratnawati (Ensiklopedia Education Review, 2024)
Law Number. 32/2009 about PPLH and Law Number. 11/2020 concerning Job Creation have been amended, and the clauses pertaining to "absolute responsibility" have been eliminated. in order to relieve companies of the burden of total accountability. In the meanwhile, fundamental criminal punishments must be followed by supplementary criminal sanctions, such as compensation for criminal conduct. This research endeavor aims to answer the following question: How can the criminal liability laws for firms that commit environmental crimes be reconstructed in a way that promotes justice? This study's methodology combines a constructivist paradigm with a normative judicial approach. The findings and analysis demonstrate that Law Number. 32/2009 addressing PPLH in conjunction with Law Number reconstructs corporate criminal culpability as offenders of environmental crimes.Keywords: Reconstruction, Accountability, Corporations, Environmental Crime